CRYSTAL CHEMISTRY OF URANYNL MOLYBDATES III. NEW STRUCTURAL THEMES IN NA6[9UO'2)2O(MOO4)2], NA6(UO2) (M0O44) - Krivovichev S.V.; Burns P.C. (My University, 2001)
Two Na uranyl molybdates, K6[(UO2)2O(MoO4)4], have been synthesized by high-temperature solid-state reactions of mixtures of Na2CO3, K2CO3, UO3 and MoO3. All three structures were solved by direct methods and refined on the basis of F2 for all unique data collected with monochromatic MoKα X-radiation and a CCD (charge-coupled device) detector. The structure of Na6[(UO2)2O(MoO4)4] was refined to an agreement factor (R1) of 4.1%, calculated using the 1969 unique observed reflections (Fo ≥ 4σF), and a goodness-of-fit (S) of 1.06. It is triclinic, space group PĪ, a 7.637(2), b 8.164(2), c 8.746(2) Å, α 72.329(5), β 79.364(5), Υ 65.795(4)°, V 472.7(2) Å3. Z = 1. The structure of Na6[(UO2)(MoO4)4] was refined to an R1 of 3.3%, calculated using the 3268 unique observed reflections (Fo ≥ 4 σ F), and a S of 0.97. It is triclinic, space group PĪ, a 7.0958(8), b 9.566(1), c 13.415(2) Å, α 73.692(2). β 86.621(2), Υ 82.940(2)°, V 867.0(2) Å3, Z = 2. The structure of K6[(UO2)2O(MoO4)4] was refined to an RI index of 4.9%. calculated using the 1833 unique observed reflections (Fo ≥ 4σ F), and a S of 0.90. It is triclinic, space group PĪ, a 7.8282(8). b 7.8298(8), c 10.302(1) Å, α 83.893(2), β 73.131(2), Υ 80.338(2)°. V 594.6(1) Å3, Z = 1. The structural connectivity of these three compounds is notable in that each exhibits themes not previously observed in uranyl compounds. The structures of both Na6[(UO2)2O(MoO4)4] and K6[(UO2)2O(MoO4)4] contain chains of polyhedra of composition [(UO2)2O(MoO4)4]6-. These chains have not been previously observed and are composed of [UrO4OUrO4] dimers consisting of two UrO5 (Ur: uranyl ion) pentagonal bipyramids sharing a common O atom. The dimers are connected into a chain by sharing vertices with MoO4 tetrahedra, with the chains linked by Na+ or K+ cations. The structure of Na6[(UO2)(MoO4)4] consists of finite clusters of composition [(UO2)2(MoO4)8]12- composed of two UrO5 pentagonal bipyramids connected by sharing vertices with MoO4 tetrahedra. The clusters in Na6[(UO2)(MoO4)4] are oriented parallel to the (001) plane and are linked through Na+ cations.
Keywords: Crystal chemistry; Uranynl molybdates